Exploring Neural Signaling Patterns and Their Physiological Origins in Fibromyalgia by Means of Functional MRI Guided by a Review of the Literature - Mara Will; Patrick W. Stroman (Brain Sciences)
Background/Objectives: Fibromyalgia (FM) is a chronic pain condition that includes symptoms of hyperalgesia and has an unknown etiology. This study aimed to further investigate the underlying neural signaling mechanisms and their relation to observed blood oxygenation-level dependent (BOLD) signal increases at the onset of functional magnetic resonance imaging (fMRI) runs. Methods: The possible neural mechanisms were first explored by reviewing the current literature. The second component of this study involved a voxel-by-voxel analysis of BOLD responses in all regions of the brain. The fMRI data were obtained from a previous study of participants with and without fibromyalgia during fMRI runs involving either a noxious heat pain stimulus or no stimulus. Results: The literature review indicates that no single factor can explain the initial BOLD signal rise observed in FM but that there are likely multiple interacting influences. These include physiological dysregulation via mechanisms, such as oxidative stress, mitochondrial dysfunction, and cytokine activity, and may involve the sympathetic nervous system. The analysis of BOLD responses demonstrated that the initial BOLD rises occur specifically in gray matter regions and are largest in regions involved with pain processing, including the right insular cortex and periaqueductal gray region. Moreover, the BOLD rise is significantly larger in people with FM prior to the application of a noxious stimulus. Conclusions: The initial rise in BOLD response demonstrates heightened metabolic demand that is exaggerated in people with FM. It appears to be influenced by cognitive factors such as anticipation and may reflect neural dysregulation, possibly involving autonomic signaling.